VIRAL DIARRHEA IN CHILDREN: PECULIARITIES OF CLINICAL PICTURE AND TACTICS OF DIETIC CORRECTION - O.V. Tikhomirova; M.K. Bekhtereva; I.V. Razd''yakonova; O.I. Nyrkova (Вопросы современной педиатрии, 2009)
This work characterizes peculiarities of clinical picture of viral diarrhea in children. Effectiveness of dietotherapy of children with acute enteric infection with use of substitutes of breast milk: “Nutrilon Low Lactose”, “Nutrilon Comfort 2”, “Nutrilon Antireflux” was studied. It was proved, that valid dietic correction results in more rapid recovery and provides maintenance of trophic status. Key words: children, viral enteric infections, dietoterapy. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(1):98-103)